2020
DOI: 10.1111/hel.12682
|View full text |Cite
|
Sign up to set email alerts
|

Application of a social media platform as a patient reminder in the treatment of Helicobacter pylori

Abstract: Background To investigate the effect of a social media platform for the treatment of Helicobacter pylori infection. Materials and Methods We enrolled 222 patients from October 2018 to June 2019, who required H pylori therapy. We used WeChat, a social media platform, as a patient reminder tool. They were randomly divided into the intervention and control groups (n = 111 per group) to compare and evaluate their disease awareness, medication adherence, incidence of adverse drug reactions, and H pylori eradication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
59
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(61 citation statements)
references
References 8 publications
0
59
2
Order By: Relevance
“…Two recent large randomized controlled trials from China demonstrated that the use of an interactive smartphone medical application 20 and text-based reminders 21 during treatment improved adherence to primary therapy. These adjunctive systems are worthy of further investigation in the United States for refractory H pylori infection and would provide information on which approaches might be more effective in certain populations compared with others; for example, based on characteristics such as age, race and ethnicity, educational level, access, and language.…”
Section: Nonadherencementioning
confidence: 99%
“…Two recent large randomized controlled trials from China demonstrated that the use of an interactive smartphone medical application 20 and text-based reminders 21 during treatment improved adherence to primary therapy. These adjunctive systems are worthy of further investigation in the United States for refractory H pylori infection and would provide information on which approaches might be more effective in certain populations compared with others; for example, based on characteristics such as age, race and ethnicity, educational level, access, and language.…”
Section: Nonadherencementioning
confidence: 99%
“…In this study, H. pylori (+) patients confirmed with positive carbon-14 (C14) breath tests and endoscopic biopsies and also showed the indications for H. pylori eradication treatment were divided into two groups: The intervention group used a social media platform as a reminder besides traditional instructions and the control group was only given traditional instructions verbally about the dose and method of medication, the precautions that should be taken during the medication regimen and information related to follow-ups. The results of this study were as follows: Compared to the control group, the intervention group had significantly better awareness of H. pylori, significantly higher treatment adherence and significantly higher eradication rate whereas there was no significant difference in terms of drug related adverse reactions [20].…”
Section: Discussionmentioning
confidence: 79%
“…pylori eradication (Wang et al, 2015). A recent study using a popular social media platform as a patient reminder at four time points during treatment acquired better eradication efficacy and compliance (Luo et al, 2020). However, it did not undergo ITT and PP analysis, and doctors still needed to record every patient's information by themselves.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study revealed that approximately 17% of patients showed poor compliance in their treatment history, primarily due to the patients’ own will and side effects (Li et al, 2018). The majority of the studies concluded that enhancing follow‐up using a telephone, short message, diary chart, and social media platforms could positively improve the eradication rate (Al‐Eidan et al, 2002; Luo et al, 2020; Wang et al, 2019) or reduce side effects (Wang et al, 2015). Particularly, intensive follow‐up requires a greater effort from the physician.…”
Section: Introductionmentioning
confidence: 99%